Educator–student communication in sex & relationship education: a comparison of teacher and peer-led interventions. (2nd October 2017) - Dobson, Emma; Beckmann, Nadin; Forrest, Simon
Abstract: This paper presents findings from a comparative study of peer- and teacher-led Sex and Relationship Education (SRE). One lesson delivered by a peer educator, and one lesson delivered by a teacher was observed with the aim of exploring the communicative process between educators and students within SRE. It is claimed that open communication between students and peer educators promotes the adoption of positive attitudes to sexual health, making it a potential alternative to teacher-led provision. Yet to our knowledge, no studies have investigated the communicative process within peer-led adolescent health interventions to examine factors underpinning its potential efficacy. The development of a coding scheme to measure the extent to which educators and students are communicating openly within SRE is used to describe the communicative process between sex educators and students, characterise differences in communication within peer- and teacher-led conditions and discuss how these differences affect student participation in SRE. Results suggest interaction of students in the peer-led condition was different to that of students receiving teacher-led SRE; and provide valuable insight into educator–student communication in the context of classroom-based SRE.